Vascular smooth muscle cells in response to cholesterol crystals modulates inflammatory cytokines release and promotes neutrophil extracellular trap formation - Jishamol Thazhathveettil; Ashok Kumar Kumawat; Isak Demirel; Allan Sirsjö; Geena Varghese Paramel (Molecular Medicine, 2024)
Abstract Background The formation and accumulation of cholesterol crystals (CC) at the lesion site is a hallmark of atherosclerosis. Although studies have shown the importance of vascular smooth muscle cells (VSMCs) in the disease atherosclerosis, little is known about the molecular mechanism behind the uptake of CC in VSMCs and their role in modulating immune response. Methods Human aortic smooth muscle cells were cultured and treated with CC. CC uptake and CC mediated signaling pathway and protein induction were studied using flow cytometry, confocal microscopy, western blot and Olink proteomics. Conditioned medium from CC treated VSMCs was used to study neutrophil adhesion, ROS production and phagocytosis. Neutrophil extracellular traps (NETs) formations were visualized using confocal microscopy. Results VSMCs and macrophages were found around CC clefts in human carotid plaques. CC uptake in VSMCs are largely through micropinocytosis and phagocytosis via PI3K–AkT dependent pathway. The uptake of CC in VSMCs induce the release inflammatory proteins, including IL-33, an alarming cytokine. Conditioned medium from CC treated VSMCs can induce neutrophil adhesion, neutrophil reactive oxygen species (ROS) and neutrophil extracellular traps (NETs) formation. IL-33 neutralization in conditioned medium from CC treated VSMCs inhibited neutrophil ROS production and NETs formation. Conclusion We demonstrate that VSMCs due to its vicinity to CC clefts in human atherosclerotic lesion can modulate local immune response and we further reveal that the interaction between CC and VSMCs impart an inflammatory milieu in the atherosclerotic microenvironment by promoting IL-33 dependent neutrophil influx and NETs formation.